2019
DOI: 10.1017/s1092852918001748
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive brain stimulation in rehabilitation of hemispatial neglect after stroke

Abstract: BackgroundNoninvasive brain stimulation can modulate neural processing within the motor cortex and thereby might be beneficial in the rehabilitation of hemispatial neglect after stroke.MethodsWe review the pertinent literature regarding the use of transcranial direct current stimulation (tDCS) and transcranial magnetic stimulation in order to facilitate recovery of hemispatial neglect after stroke.ResultsTwenty controlled trials (including 443 stroke patients) matched our inclusion criteria. Methodology and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 44 publications
2
8
0
Order By: Relevance
“…In sum, bilateral stimulation is superior to unilateral protocols. Similarly, a previous meta-analysis demonstrates the superior effectiveness of bilateral tDCS/rTMS for improving visuo-spatial ability following stroke [ 39 ]. However, a current meta-analysis indicates that bilateral tDCS is inferior to unilateral tDCS for improving motor learning in stroke patients [ 74 ].…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…In sum, bilateral stimulation is superior to unilateral protocols. Similarly, a previous meta-analysis demonstrates the superior effectiveness of bilateral tDCS/rTMS for improving visuo-spatial ability following stroke [ 39 ]. However, a current meta-analysis indicates that bilateral tDCS is inferior to unilateral tDCS for improving motor learning in stroke patients [ 74 ].…”
Section: Discussionmentioning
confidence: 80%
“…Despite its limitations, the theory of interhemispheric imbalance and rivalry provides the most often used theoretical framework for the application of noninvasive brain stimulation in stroke rehabilitation [ 37 ]. Previous studies have demonstrated that several stroke-induced deficiencies, such as upper limb impairment or visuo-spatial disabilities may be successfully restored by application of non-invasive brain stimulation within this concept [ 38 , 39 ]. The available data (see previous subchapter) indicates that a similar application may also be useful for supporting gait, balance, and lower limbs´ motor functioning.…”
Section: Introductionmentioning
confidence: 99%
“…Meta-analyses and systematic reviews also suggest a beneficial effect of rTMS on USN. 61,63,64,66,68–71…”
Section: Augmenting Recovery: State Of the Evidence On Usn Interventionmentioning
confidence: 99%
“…Transcranial magnetic stimulation (TMS) and transcranial direct current stimulation (tDCS) techniques have been used in the past years to improve motor recovery in stroke patients, often jointly with standard physiotherapy practice. However, while at the single study level the administration of TMS and tDCS treatments appear beneficial to patients in motor and/or cognitive domain, meta-analysis results have shown that these effects are rather limited or, in some cases, even non-existent (e.g., [11][12][13][14][15]). It should be noticed that these stimulation protocols have been developed on the basis of the conviction that either the interhemispheric competition or the vicariation model might be the one that best predicts recovery [9].…”
Section: Stroke Recovery Models and Efficiency Of Non-invasive Rehabilitation Protocolsmentioning
confidence: 99%